Does massage warm-up adequately prepare muscles for high intensity cycling exercise? - Terblanche, E.; Bester, M. M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Our results suggest that there are little, if any, differences in physiological variables following a spinning or massage warm-up. However, cyclists performed significantly better after the spinning warm-up compared to the massage warm-up. It is possible that the massage did not sufficiently increase peripheral circulation and muscle temperature - factors that are associated with increased oxygen delivery to the muscles (3). We therefore conclude that a 15-min massage of the lower extremities does not prepare the muscles optimally for short duration, high intensity exercise.